2005
DOI: 10.1523/jneurosci.0377-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Using Functional Magnetic Resonance Imaging to Assess Adaptation and Size Invariance of Shape Processing by Humans and Monkeys

Abstract: Functional magnetic resonance imaging in awake monkeys and humans was used to compare object adaptation in shape-sensitive regions of these two species under identical and different size conditions. Object adaptation was similar in humans and monkeys under both conditions. Neither species showed complete size invariance, in agreement with single-cell studies. Both the macaque inferotemporal (IT) complex and human lateral occipital complex (LOC) displayed an anteroposterior gradient in object adaptation and siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
128
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(141 citation statements)
references
References 69 publications
11
128
2
Order By: Relevance
“…The correspondence between fMRI activation patterns in monkeys and humans in previous studies (e.g., [53][54][55][56][57][58] and, partly, in our work is encouraging, although it does not necessarily imply that the underlying behavioral strategies and neuronal activity in the two species are the same. Nevertheless, monkey fMRI provides a crucial control for the common interpretation of human imaging and monkey electrophysiology data.…”
Section: Discussionsupporting
confidence: 73%
“…The correspondence between fMRI activation patterns in monkeys and humans in previous studies (e.g., [53][54][55][56][57][58] and, partly, in our work is encouraging, although it does not necessarily imply that the underlying behavioral strategies and neuronal activity in the two species are the same. Nevertheless, monkey fMRI provides a crucial control for the common interpretation of human imaging and monkey electrophysiology data.…”
Section: Discussionsupporting
confidence: 73%
“…When subjects were performing the high-acuity task (Vanduffel et al, 2001), the target was replaced with a yellow bar whose size was adapted for each subject based on psychophysical testing in the scanner (Sawamura et al, 2005). To reduce the amount of head motion during the scanning sessions, the subjects were asked to bite an individually molded bite bar fixed on the scanner table.…”
Section: Participantsmentioning
confidence: 99%
“…Six of these subjects (1, 3, 19, 20, 21, 22 in Table 1) were scanned while performing a high-acuity task (Vanduffel et al, 2001) during which the stimuli used in the main experiment were presented. They were required to interrupt a light beam with their right thumb when a small yellow bar, presented in the middle of the screen changed orientation (for 1 s) from horizontal to vertical at random intervals between 2 and 10 s. Psychophysical tests performed in the scanner indicated that performance level (percentage correct detection of orientation change) decreased and reaction time increased with decreasing bar size, suggesting that these are sensitive indicators of the subjects' attentional state (Sawamura et al, 2005). Before the scanning session subjects performed a psychophysical test in the scanner in which the level of performance at different bar sizes was tested.…”
Section: Control Experiment: High-acuity Task (N ϭ 6)mentioning
confidence: 99%
“…To control for possible differences in attention during presentation of the action and control stimuli, we performed a control experiment in which monkey M5 performed an acuity task ( Vanduffel et al, 2001;Sawamura et al, 2005), whereas the action stimuli were presented in the background. The orientation of the bar changed to vertical at random moments, which the monkey had to indicate by a manual response.…”
Section: Additional Functional Characteristics Of Less Known or Unknomentioning
confidence: 99%